Do the European and Dutch rules on variable remuneration of financial institutions match and can remuneration be regulated on a European level? - Kromwijk, D. E. M.; Oostwouder, W. J. (Indonesian Journal of International Law, 2021)
The special committee of inquiry into the financial crisis (Tijdelijke commissie onderzoek financieel stelsel), better known as the De Wit Committee was in charge of investigating for the second chamber of the Dutch Parliament how the credit crisis had originated and how a future crisis could be prevented. In its report, the Committee paid special attention to the influence of remuneration on the crisis. In its final report, three of the twenty five recommendations concerned remuneration. Not only in the Netherlands was there attention for the incentives of remuneration and their role in the credit crisis, but also in the rest of the world. There are three different theories which try to explain the existence of variable remuneration: the agency theory, the market theory and the corporate governance theory. This article describes the European and Dutch rules on variable remuneration of executive board members and where possible also of employee remuneration. However, these rules are not always clear-cut. In this article, discrepancies between the European and the Dutch rules will be discussed. In this article, variable remuneration will thus be considered as a tool to solve the agency problem. The total remuneration (including the variable remuneration) can be seen as an instrument to attract and bind board members.